Data fabric architectures web-driven applications - Sharma, Vandana; Balusamy, Balamurugan; Thomas, J. Joshua 1973-; Atlass, L. Godlin (De Gruyter, 2023)
The immense increase on the size and type of real time data generated across various edge computing platform results in unstructured databases and data silos. This edited book gathers together an international set of researchers to investigate the possibilities offered by data-fabric solutions; the volume focuses in particular on data architectures and on semantic changes in future data landscapes